Embodied Services of Greenhouse Gas Emissions: A Case Study of the EU Member Countries - Su, Meirong; Zheng, Ying; Pauleit, Stephan; Hao, Yan; Yin, Xuemei; Liu, Gengyuan; Zhang, Yan (Journal of Environmental Accounting and Management, 2026)
Decreasing Greenhouse Gas (GHG) emissions is a globally agreed goal for mitigating climate change. Considering previous disputes between countries and the negative emotions subconsciously injected into those responsible for the management of the problem, it is useful to reconsider how to ensure that more countries actively contribute to climate change mitigation. Here, we propose a new concept of ‘embodied services of GHG emissions’ to express the underlying services associated with GHG emissions. Based on a developed assessment framework and indicators, we rank the 28 EU member countries in terms of embodied services of GHG emissions. Analyzing these countries’ results geospatially presented an archaeopteryx pattern, where countries on the two wings have the highest levels of embodied services while those on the back and tail have the lowest. The results are also analyzed for each country over time allowing efforts made by those countries to be displayed in different aspects. We believe that the proposed concept has effective resolution for both spatial and temporal scales. We anticipate that countries’ willingness to engage in climate change mitigation will be stimulated by targeting improvement of embodied services of GHG emissions as an additional, beneficial goal, which also embodies equality and incentivizing aspects.